Islam between divine message and history - Sharafī, ʿAbd al-Majīd (Central European University Press, 2005)
Pt. 1. The theoretical and historical background -- The Mohammedan mission -- The characteristics of the Mohammedan mission -- The issue of legislation (Tashric) -- The seal of prophecy -- Pt. 2. The Mission in History -- The Prophet's caliphate -- Institutionalizing religion -- Theorizing for the institution -- Epilogue.